Educadores sociais que atuam no contraturno escolar junto a crianças e adolescentes: os sentidos e significados atribuídos a sua atividade - Dietz, Karin Gerlach (2013)
The present study intends to extend the knowledge concerning the practice performed by social educators by approaching the meanings and senses constructed by a social educator who works during the school s extra-curricular period, performing activities developed in an institution that serves children and adolescents at vulnerable and social risk. This institution, established and located in a suburb near the city of São Paulo, is a public foundation whose mission and guidelines are focused on ensuring the rights of children and youths. The theoretical perspective adopted in the study is that of Socio-Historical Psychology. Data was produced through interviews with a social educator: a man named Daniel, with eight years of experience in the institution having been responsible for circus workshops. The material was recorded, transcribed, systematized and analyzed according to Aguiar and Ozella s (2006, 2013) proposal, aiming to build several nuclei of meaning, in order to achieve, gradually, more specific areas of meaning. Through the analysis of the data, it was noted that Daniel initially came to this position through financial necessity and because of this, did not perceive himself as a social educator. He began his career without any training or even information about the area, feeling that, to perform his duties, he needed self-improvement. He reveals a scenario of uncertainty, which can be considered professional and, at the same time, not. He requires theoretical support but he does not have access to it in the proper way and has no time to exchange experience with his fellow workers. The intention of making a transformative praxis is present, however, this path is still tenuous and poorly defined, unable to uncover social inequalities and be an effective means of change. The theory itself that supports this practice needs to be revised, considering the current dichotomy between society and education. We need to think that social education, although not regulated as a profession, needs to be understood as an activity that requires extensive studies, because it depends not only on a practical skill, but also on a critical stance towards society